Composite aerogel type oxygen reduction catalyst as well as preparation method and application thereof

By combining γ-graphite monoalkyne and multi-wall carbon nanotubes into an aerogel and adding pyrrole, an efficient, stable and low-cost ORR catalyst was prepared, which solved the durability of existing catalysts in high temperature and high pressure environments. , achieving improvements in fuel cell performance.

CN119400882APending Publication Date: 2025-02-07SHANGHAI UNIV OF ENG SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411549975.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing ORR catalysts have durability problems in high temperature, high pressure or complex environments and are costly, which limits the development of fuel cells.

Method used

Compound aerogel-type oxygen reduction catalyst was prepared by combining γ-graphite monoalkyne (γ-GY) and multi-walled carbon nanotubes (MWCNT) into an aerogel and combined with the addition of pyrrole. This method is prepared by hydrothermal method, which is simple to operate, low cost, and can accurately control the compound ratio and reaction conditions.

Benefits of technology

It improves the catalytic activity and stability of the catalyst, extends the service life, reduces maintenance costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400882A_ABST
    Figure CN119400882A_ABST
Patent Text Reader

Abstract

The invention relates to a composite aerogel type oxygen reduction catalyst and a preparation method and application thereof.According to the composite aerogel type oxygen reduction catalyst and the preparation method and application thereof, the composite proportion of gamma-GY and MWCNT and doping of nitrogen heteroatoms are accurately controlled, and hydrothermal reaction conditions are optimized; the gamma-GY / MWCNT composite aerogel type oxygen reduction catalyst which shows remarkable advantages and breakthrough in the aspects of structure, performance, synthesis process and the like is prepared. Compared with the prior art, the method is simple to operate, low in cost and easy to realize large-scale production. The prepared aerogel catalyst combines the advantages of the carbon nanomaterial and the aerogel, has high specific surface area and mesoporous structure, and excellent oxygen reduction catalytic performance and stability, and can be used as a fuel cell cathode catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cell science and technology, and in particular to a composite aerogel-type oxygen reduction catalyst and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cells (PEMFCs) are considered to be one of the key technologies for achieving sustainable energy and carbon neutrality due to their high energy conversion efficiency and zero emission characteristics. However, the performance of PEMFCs is limited by the oxygen reduction reaction (ORR) at the cathode, so the development of efficient ORR catalysts is the key to the commercialization of fuel cells. Although significant progress has been made in the research of ORR catalysts over the past few decades, the development of catalysts with both excellent activity and good durability remains a huge challenge.

[0003] Pt-based catalysts are currently the most common ORR catalysts. Although Pt-based catalysts have excellent performance, we must also face up to their existing problems. First, as a precious metal, Pt has small geological reserves, which will lead to a significant increase in costs when used on a large scale, which is not conducive to its large-scale application in the commercial field, further limiting the development of proton exchange membrane fuel cells. Secondly, the corrosion resistance of Pt-based catalysts is not ideal. Under specific conditions such as acid or alkali, they are easily affected by oxidation or reduction and become ineffective, which greatly reduces the stability and service life of the catalyst. In order to solve these problems, researchers are actively looking for easily available, cheap and efficient alternatives to Pt / C catalysts.

[0004] The Chinese patent CN115986148A discloses a low-platinum graphene ORR catalyst and its preparation method and application. The invention uses polyimide film and chloroplatinic acid as raw materials, and prepares a low-platinum graphene oxygen reduction catalyst by laser etching technology and electrodeposition. The invention is simple and easy, low cost, suitable for industrial production, and the prepared low-platinum graphene oxygen reduction catalyst has good oxygen reduction catalytic performance. However, its durability problem cannot be ignored. Under high temperature, high pressure or complex environment, the structure of graphene and platinum particles may be fatigued due to the influence of thermal stress and mechanical stress, resulting in a decrease in its conductivity and stability. At the same time, platinum particles may also be affected by environmental factors and aggregate or deactivate, thereby affecting the catalytic performance of the catalyst.

[0005] Chinese patent CN110492112 discloses an ORR composite catalyst and its preparation method, which combines mesoporous hollow carbon spheres and transition metal nitrides, wherein the mesoporous hollow carbon spheres provide the catalyst with a larger specific surface area and more active sites, while the transition metal nitride enhances the oxygen reduction ability of the catalyst through its unique electronic structure. However, the preparation process of this invention is relatively complicated, which increases the difficulty and cost of preparation; secondly, the stability of the catalyst is insufficient, and the performance may be degraded due to environmental factors such as temperature and humidity during use; in addition, the size of the catalyst is difficult to control.

[0006] The preparation method of graphite carbon ORR electrocatalytic nanomaterials disclosed in Chinese patent CN115924900A, the raw materials of the invention are easily available and cheap, the process is simple, suitable for large-scale production, and the prepared materials show excellent oxygen reduction electrocatalytic performance under both acidic and alkaline conditions. However, there are still some challenges in terms of stability and selectivity of the material. In terms of stability, graphite carbon ORR electrocatalytic nanomaterials may face problems such as structural changes, deactivation or dissolution under long-term use or complex environments; in terms of selectivity, although graphite carbon ORR electrocatalytic nanomaterials show good catalytic activity in some reactions, they may have low operating efficiency or low selectivity in other reactions.

[0007] Therefore, the synthesis of ORR catalysts with high catalytic activity, low cost, simple preparation operation and high stability is of great significance to the development of fuel cells. Summary of the invention

[0008] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a composite aerogel-type oxygen reduction catalyst and a preparation method and application thereof, so as to further improve the catalytic activity and stability of the ORR catalyst.

[0009] During the course of conception, the applicant believed that the present invention retains the excellent properties of carbon nanomaterials by compounding γ-graphite (γ-GY) and multi-walled carbon nanotubes (MWCNT) into aerogel. At the same time, the high specific surface area and mesoporous structure of the aerogel provide sufficient catalytic interface for the reaction, and the addition of pyrrole improves the activity and stability of the catalytic oxygen reduction reaction.

[0010] The purpose of the present invention can be achieved by the following technical solutions:

[0011] In one aspect, the present invention provides a method for preparing a composite aerogel-type oxygen reduction catalyst, comprising the following steps:

[0012] S1, ultrasonically treating an acidified γ-graphite aqueous solution to form a suspension, and mixing the acidified γ-graphite suspension with acidified multi-walled carbon nanotubes and pyrrole to form a dispersion;

[0013] S2, using the dispersion prepared in S1 to prepare a γ-graphene monoacetylene / multi-walled carbon nanotube composite hydrogel by a hydrothermal method;

[0014] S3, purifying and freeze-drying the hydrogel obtained in S2 to obtain a γ-graphite monoacetylene / multi-walled carbon nanotube composite aerogel catalyst.

[0015] Furthermore, in S1, the ultrasonic time for preparing the suspension is 10 to 60 min, and the concentration of the suspension is 5 to 20 mg / mL.

[0016] Furthermore, in S1, the time of the ultrasonic treatment after mixing is 10 to 60 minutes, and the temperature of the ultrasonic treatment after mixing is 15 to 50°C.

[0017] Furthermore, in S1, the mass ratio of the acidified γ-graphite monoyne to the acidified multi-walled carbon nanotubes in the acidified γ-graphite monoyne aqueous solution is 1 to 6:1.

[0018] Furthermore, in S1, the volume ratio of the acidified γ-graphite monoacetylene aqueous solution to pyrrole is 40:1-6.

[0019] Furthermore, in S2, the size of the hydrothermal kettle used in the hydrothermal method is 10-100 mL, the reaction temperature is 120-240° C., and the reaction time is 24-72 h.

[0020] Furthermore, in S3, the specific step of purification includes: the hydrogel obtained in S2 is washed by exchanging deionized water and ethanol solvent, and the washing time is 5 to 10 days.

[0021] Furthermore, in S3, the freeze-drying time is 12 to 36 hours.

[0022] On the other hand, the present invention also provides a composite aerogel-type oxygen reduction catalyst obtained by the above-mentioned preparation method.

[0023] On the other hand, the present invention also provides an application of the composite aerogel-type oxygen reduction catalyst obtained by the above-mentioned preparation method in a fuel cell.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention prepares an ORR aerogel catalyst that shows significant advantages and breakthroughs in structure, performance, and preparation process by precisely controlling the composite ratio of γ-GY and MWCNT and optimizing the hydrothermal reaction conditions. This innovative design not only retains the high specific surface area, excellent conductivity, and mechanical strength of carbon nanomaterials, but also gives the catalyst aerogel special properties. The prepared catalyst has the characteristics of high specific surface area and mesoporous structure, high reaction efficiency, and strong modifiability, making it have great application value in the fields of energy conversion and storage, environmental protection, etc.

[0026] (2) In terms of structure and performance, γ-GY itself has a certain ORR ability, while MWCNT not only has excellent conductivity and mechanical strength, but also can provide a large number of attachment sites for γ-GY, thereby increasing the contact area between the catalyst and the reactant. Therefore, the synergistic effect between MWCNT and γ-GY significantly improves the electrocatalytic performance of the catalyst. At the same time, after γ-GY is made into aerogel, it not only retains its unique electronic properties, but also has the advantages of light weight, large surface area, high aspect ratio, straight edges, and ideal surface rules. The layered three-dimensional structure of the aerogel further increases the specific surface area of ​​the sample and provides more active sites for the ORR reaction. In addition, the addition of pyrrole, on the one hand, promotes the gelation of the material, and on the other hand, realizes the doping of N atoms, thereby improving the activity and stability of the catalytic oxygen reduction reaction. These characteristics enable the γ-GY / MWCNT composite aerogel catalyst to maintain stable catalytic performance in practical applications, extend service life, and reduce maintenance costs.

[0027] (3) In terms of preparation technology, the hydrothermal method adopted in the present invention is not only simple to operate, but also low in cost and the raw materials are readily available. Compared with the traditional method, the steps of this method are controllable and easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the morphology of the γ-GY / MWCNT aerogel prepared in Example 1;

[0029] Figure 2 This is the Raman spectrum of the γ-GY / MWCNT aerogel prepared in Example 1;

[0030] Figure 3 This is the X-ray diffraction pattern (XRD) of the γ-GY / MWCNT aerogel prepared in Example 1;

[0031] Figure 4 This is a scanning electron microscope image (SEM) of the γ-GY / MWCNT aerogel prepared in Example 1;

[0032] Figure 5 The transmission electron microscope image (TEM) and high-resolution transmission electron microscope image (HRTEM) of the γ-GY / MWCNT aerogel prepared in Example 1;

[0033] Figure 6 X-ray photoelectron spectroscopy (XPS) of the γ-GY / MWCNT aerogel prepared in Example 1;

[0034] Figure 7 The nitrogen adsorption-desorption isotherm and pore size distribution diagram (BET) of the γ-GY / MWCNT aerogel prepared in Example 1;

[0035] Figure 8 The cyclic voltammetry curve of the γ-GY / MWCNT aerogel prepared in Example 1 under a nitrogen atmosphere;

[0036] Fig. 9 The cyclic voltammetry curve of the γ-GY / MWCNT aerogel prepared in Example 1 under an oxygen atmosphere;

[0037] Fig.10 The linear voltammetric curve of the γ-GY / MWCNT aerogel prepared in Example 1 at 1600 rpm in an oxygen atmosphere;

[0038] Fig.11 is the Tafel slope diagram of the γ-GY / MWCNT aerogel prepared in Example 1;

[0039] Fig.12 This is a comparison diagram of the linear voltammetric curves of the γ-GY / MWCNT aerogel prepared in Example 1, γ-GY and MWCNT at 1600 rpm. DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Any features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.

[0041] The γ-graphene (γ-GY) used in the following examples was prepared according to the literature: He S, Wu B, Xia Z, et al. One-pot synthesis of gamma-graphyne supported Pd nanoparticles with high catalytic activity [J]. Nanoscale Advances, 2023, 5 (9): 2487-2492. The reaction chemical equation is as follows:

[0042]

[0043] Acidified γ-GY was prepared according to the literature: Qi H, Yu P, Wang Y, et al. Graphdiyne oxides as excellent substrate for electroless deposition of Pd clusters with high catalytic activity [J]. Journal of the American Chemical Society, 2015, 137(16): 5260-5263.

[0044] Acidized carbon nanotubes (MWCNT) were prepared according to the literature: Hummers WS, Offeman RE. Functionalized graphene and graphene oxide: materials synthesis [J]. J Am Chem Soc, 1958, 80: 1339-1344.

[0045] Example 1

[0046] The present invention provides a method for preparing an oxygen reduction composite aerogel catalyst, and the specific preparation steps are as follows:

[0047] Under nitrogen (purity ≥ 99%) gas environment, the substrate hexabromobenzene (551.5 mg, 1 mmol), butynedioic acid (1140.6 mg, 10 mmol), catalyst bistriphenylphosphine palladium dichloride (210.6 mg, 0.3 mmol) and cuprous iodide (114.3 mg, 0.6 mmol) were placed in a Schlenk bottle; solvent N, N-dimethylformamide (10 mL) and triethylamine (2.1 mL) were added to dissolve. The solution was evacuated (4 times, 25 s each time) and stirred at 60 ° C for 24 h; after the reaction, a black solid was produced, which was then centrifuged, ultrasonicated with benzene, and repeatedly washed with N, N-dimethylformamide and a large amount of water until the centrifuge liquid was transparent and colorless, and the crude product γ-graphite monoyne was obtained by filtration; the crude product was refluxed with 6M sodium hydroxide for 2 h, then refluxed with 4M hydrochloric acid for 2 h, and finally refluxed with 6M sodium hydroxide for 2 h, and then filtered and evaporated to obtain the target product γ-GY.

[0048] Mix according to the ratio of m(γ-GY):m(KMnO4):V(H2SO4):V(HNO3) of 500mg:500mg:75mL:25mL. First, mix concentrated H2SO4 and concentrated HNO3, and slowly add γ-GY after cooling to room temperature, and then add KMnO4 in small amounts and multiple times. Stir the mixture vigorously in an 80℃ oil bath for 24h. After the reaction, cool the mixture to room temperature, and then neutralize it with NaOH in an ice bath to pH 8. A large amount of salt will be produced in the process. Use a filter membrane with a larger pore size to remove most of the salt by suction filtration, concentrate the mixture, and use a dialysis bag to dialyze for one week to remove inorganic acid and all impurities, and then concentrate it to 10mg / mL to obtain the acidified γ-GY aqueous solution.

[0049] MWCNT (5g) and NaNO3 (3.5g) were suspended in concentrated H2SO4 (150mL), then stirred vigorously in an ice-water bath for 60min, and KMnO4 (20g) was added in small amounts several times. Then stirred at room temperature (25°C), 300mL of water was slowly added after 120min, and H2O2 (3%, 500mL) was added. After stirring for 60min, the solution was centrifuged at 10000rpm to precipitate the acidified MWCNT, and then purified by water dialysis for one week, and then centrifuged at 5000rpm for 10min to remove the undispersed carbon nanotube bundles. Finally, the acidified MWCNT powder was obtained by rotary evaporation.

[0050] 10 mL of 10 mg / mL acidified γ-GY aqueous solution was taken and ultrasonicated for 30 min to form a suspension, and then 25 mg of acidified MWCNT (m γ-GY :m MWCNT =4:1), and 1mL of pyrrole (re-distilled before use). The mixture was ultrasonicated at 25°C for 30min to form a uniform dispersion. The mixture was then placed in a 25mL reactor and kept at a constant temperature of 180°C for 48h. After the reaction, a γ-GY / MWCNT composite hydrogel was obtained. The obtained γ-GY / MWCNT composite hydrogel was then solvent exchanged with anhydrous ethanol and deionized water for 7d to remove all impurities, and then freeze-dried for 24h to obtain a γ-GY / MWCNT composite aerogel catalyst.

[0051] Figure 1 This is the morphology of the γ-GY / MWCNT aerogel prepared in Example 1, which clearly shows the three-dimensional morphology of the γ-GY / MWCNT aerogel. This unique structure is a significant sign of the successful preparation of the aerogel material.

[0052] Figure 2This is the Raman spectrum of the γ-GY / MWCNT aerogel prepared in Example 1. Two characteristic peaks related to carbon nanotubes can be clearly observed. The two peaks are located at about 1345 cm -1 and 1580cm -1 Specifically, at about 1345cm -1 The peak is called the D band peak, which reveals the sp 3 Introduction of hybridized carbon atoms or sp 2 The intensity of the D band peak directly reflects the degree of defects in the carbon nanotube structure and provides us with important information about its structural integrity. -1 The G band peak near represents the sp 2 Hybridized carbon atoms cause E 2g The regular graphite structure of the vibration mode, the intensity of the G band peak is closely related to the integrity of the carbon nanotubes; I D / I G The ratio is an important parameter to measure the disorder degree of carbon nanomaterials. The smaller the value, the more ordered the structure of the carbon material is and the fewer defects it has. The smaller the ratio of the D band peak intensity to the G band peak intensity, the more the integrity of the carbon nanotubes in the aerogel is confirmed. In addition, it is worth noting that at about 2689 cm -1 A weaker peak, the Y peak, was also observed at γ-GY / MWCNT. This peak is generated by the stretching vibration of sp-hybridized carbon atoms in conjugated acetylenic bonds. Its existence fully proves that the aerogel also contains γ-GY. Through Raman spectroscopy analysis, we can confirm that the γ-GY / MWCNT aerogel not only retains the complete carbon nanotube structure, but also successfully introduces the γ-GY component, indicating that the preparation of γ-GY / MWCNT aerogel is successful.

[0053] Figure 3 This is the X-ray diffraction (XRD) diagram of the γ-GY / MWCNT aerogel prepared in Example 1. It can be clearly observed from the figure that the peak at 21.9° corresponds to the (002) crystal plane of γ-GY, while the peaks at 28.9° and 41.5° correspond to the (002) crystal plane and (100) crystal plane of carbon nanotubes, respectively. The appearance of these data fully proves that the structures of γ-GY and carbon nanotubes are relatively completely preserved in the aerogel.

[0054] Figure 4This is a scanning electron microscope image (SEM) of the γ-GY / MWCNT aerogel prepared in Example 1. The three-dimensional structure of the γ-GY / MWCNT aerogel can be clearly seen from the figure. This structure not only increases the specific surface area of ​​the product and can increase the catalytic activity of the aerogel, but also provides a large number of attachment sites for nanoparticles, which is conducive to further expanding its application field.

[0055] Figure 5 (A) is a transmission electron microscopy (TEM) image of the γ-GY / MWCNT aerogel prepared in Example 1. From the image, the overlapping appearance of the nanosheets can be clearly observed, showing a unique structural feature; the high-resolution transmission electron microscopy image (HRTEM) Figure 5 (B), we can clearly see the presence of MWCNT, which further confirms the successful introduction of carbon nanotubes into the aerogel; and in the high-resolution transmission electron microscopy image (HRTEM) Figure 5 In (C), clear lattice fringes can be observed on the sample. After measurement, the spacing between these fringes, i.e., the lattice spacing, is 0.354 nm, which is consistent with the spacing of the γ-GY (002) crystal plane. Figure 5 It shows that the preparation of γ-GY / MWCNT aerogel is successful and its structural properties are effectively retained and displayed.

[0056] Figure 6 X-ray photoelectron spectrum (XPS) of the γ-GY / MWCNT aerogel prepared in Example 1: (A) full spectrum; (B) C1s spectrum; (C) N1s spectrum. Figure 6 The data in (A) show that after adding pyrrole, the prepared γ-GY / MWCNT aerogel sample not only shows the peaks of elements such as C and O, but also clearly shows the peak of N element, confirming the successful doping of N atoms in the aerogel. Figure 6 In (B), the peaks were separated to obtain four peaks at 283.70 eV, 284.91 eV, 285.95 eV and 287.98 eV, representing CC (sp 2 ), CC(sp), CN and C=O bonds; First, the peak at 283.80 eV represents CC(sp 2 ) bond, which is the main bonding mode in carbon nanotubes. 2The peak is composed of hybridized carbon atoms, so the high intensity of this peak indicates that the carbon nanotubes are well retained in the aerogel; secondly, the peak at 284.91eV corresponds to the CC (sp) bond, and the peak at 287.98 corresponds to the C=O bond, which corresponds to the high-resolution C1s spectrum of γ-GY, indicating that γ-GY exists relatively intact in the aerogel; finally, the sub-peak at 285.95eV can be attributed to the CN bond formed by carbon atoms and heteroatoms N. The existence of this peak is direct evidence of N doping, which shows that N elements have been successfully incorporated into the molecular structure of the aerogel in a bonding manner. In the high-resolution N1s spectrum of the sample Figure 6 Three characteristic peaks were observed in (C), namely pyridinic-N represented by 396.95 eV, pyrrolic-N represented by 398.96 eV, and graphitic-N represented by 400.32 eV, indicating that the realization of nitrogen atom doping can improve the activity and stability of the catalytic oxygen reduction reaction.

[0057] Figure 7 The nitrogen adsorption-desorption isotherm (A) and pore size distribution diagram (B) of the γ-GY / MWCNT aerogel prepared in Example 1 are shown in FIG. Figure 7 (A) has a more obvious hysteresis loop, belonging to the type IV isotherm, and the synthesized γ-GY / MWCNT aerogel has a mesoporous structure; Figure 7 (B) The pore size distribution shows that the pore size is mainly distributed in the range of 3 to 30 nm; the data show that the surface area of ​​the sample is 112.657 cm 3 / g, and the average pore size is 3.844nm.

[0058] Example 2

[0059] The present invention provides a method for preparing an oxygen reduction composite aerogel catalyst, and the specific preparation steps are as follows:

[0060] Under nitrogen (purity ≥ 99%) gas environment, the substrate hexabromobenzene (551.5 mg, 1 mmol), butynedioic acid (1140.6 mg, 10 mmol), catalyst bistriphenylphosphine palladium dichloride (210.6 mg, 0.3 mmol) and cuprous iodide (114.3 mg, 0.6 mmol) were placed in a Schlenk bottle; solvent N, N-dimethylformamide (10 mL) and triethylamine (2.1 mL) were added to dissolve. The solution was evacuated (4 times, 25 s each time) and stirred at 60 ° C for 24 h; after the reaction, a black solid was produced, which was then centrifuged, ultrasonicated with benzene, and repeatedly washed with N, N-dimethylformamide and a large amount of water until the centrifuge liquid was transparent and colorless, and the crude product γ-graphite monoyne was obtained by filtration; the crude product was refluxed with 6M sodium hydroxide for 2 h, then refluxed with 4M hydrochloric acid for 2 h, and finally refluxed with 6M sodium hydroxide for 2 h, and then filtered and evaporated to obtain the target product γ-GY.

[0061] Mix according to the ratio of m(γ-GY):m(KMnO4):V(H2SO4):V(HNO3) of 500mg:500mg:75mL:25mL. First, mix concentrated H2SO4 and concentrated HNO3, and slowly add γ-GY after cooling to room temperature, and then add KMnO4 in small amounts and multiple times. Stir the mixture vigorously in an 80℃ oil bath for 24h. After the reaction, cool the mixture to room temperature, and then neutralize it with NaOH in an ice bath to pH 8. A large amount of salt will be produced in the process. Use a filter membrane with a larger pore size to remove most of the salt by suction filtration. Concentrate the mixture and dialyze it for one week using a dialysis bag to remove inorganic acid and all impurities. Then concentrate it to 5mg / mL to obtain an acidified γ-GY aqueous solution.

[0062] MWCNT (5g) and NaNO3 (3.5g) were suspended in concentrated H2SO4 (150mL), then stirred vigorously in an ice-water bath for 60min, and KMnO4 (20g) was added in small amounts several times. Then stirred at room temperature (25°C), 300mL of water was slowly added after 120min, and H2O2 (3%, 500mL) was added. After stirring for 60min, the solution was centrifuged at 10000rpm to precipitate the acidified MWCNT, and then purified by water dialysis for one week, and then centrifuged at 5000rpm for 10min to remove the undispersed carbon nanotube bundles. Finally, the acidified MWCNT powder was obtained by rotary evaporation.

[0063] 20 mL of 5 mg / mL acidified γ-GY aqueous solution was taken and ultrasonicated for 10 min to form a suspension. Then 100 mg of acidified MWCNT (m γ-GY :m MWCNT=1:1), and 3mL of pyrrole (re-distilled before use). The mixture was ultrasonicated at 50°C for 10min to form a uniform dispersion. The mixture was then placed in a 50mL reactor and kept at a constant temperature of 120°C for 72h. After the reaction, a γ-GY / MWCNT composite hydrogel was obtained. The obtained γ-GY / MWCNT composite hydrogel was then solvent exchanged with anhydrous ethanol and deionized water for 7d to remove all impurities, and then freeze-dried for 36h to obtain a γ-GY / MWCNT composite aerogel catalyst.

[0064] Example 3

[0065] The present invention provides a method for preparing an oxygen reduction composite aerogel catalyst, and the specific preparation steps are as follows:

[0066] Under nitrogen (purity ≥ 99%) gas environment, the substrate hexabromobenzene (551.5 mg, 1 mmol), butynedioic acid (1140.6 mg, 10 mmol), catalyst bistriphenylphosphine palladium dichloride (210.6 mg, 0.3 mmol) and cuprous iodide (114.3 mg, 0.6 mmol) were placed in a Schlenk bottle; solvent N, N-dimethylformamide (10 mL) and triethylamine (2.1 mL) were added to dissolve. The solution was evacuated (4 times, 25 s each time) and stirred at 60 ° C for 24 h; after the reaction, a black solid was produced, which was then centrifuged, ultrasonicated with benzene, and repeatedly washed with N, N-dimethylformamide and a large amount of water until the centrifuge liquid was transparent and colorless, and the crude product γ-graphite monoyne was obtained by filtration; the crude product was refluxed with 6M sodium hydroxide for 2 h, then refluxed with 4M hydrochloric acid for 2 h, and finally refluxed with 6M sodium hydroxide for 2 h, and then filtered and evaporated to obtain the target product γ-GY.

[0067] Mix according to the ratio of m(γ-GY):m(KMnO4):V(H2SO4):V(HNO3) of 500mg:500mg:75mL:25mL. First, mix concentrated H2SO4 and concentrated HNO3, and slowly add γ-GY after cooling to room temperature, and then add KMnO4 in small amounts and multiple times. Stir the mixture vigorously in an 80°C oil bath for 24h. After the reaction, cool the mixture to room temperature, and then neutralize it with NaOH in an ice bath to pH 8. A large amount of salt will be produced in the process. Use a filter membrane with a larger pore size to remove most of the salt by suction filtration. Concentrate the mixture and dialyze it for one week using a dialysis bag to remove inorganic acid and all impurities. Then concentrate it to 20mg / mL to obtain the acidified γ-GY aqueous solution.

[0068] MWCNT (5g) and NaNO3 (3.5g) were suspended in concentrated H2SO4 (150mL), then stirred vigorously in an ice-water bath for 60min, and KMnO4 (20g) was added in small amounts several times. Then stirred at room temperature (25°C), 300mL of water was slowly added after 120min, and H2O2 (3%, 500mL) was added. After stirring for 60min, the solution was centrifuged at 10000rpm to precipitate the acidified MWCNT, and then purified by water dialysis for one week, and then centrifuged at 5000rpm for 10min to remove the undispersed carbon nanotube bundles. Finally, the acidified MWCNT powder was obtained by rotary evaporation.

[0069] 3 mL of 20 mg / mL acidified γ-GY aqueous solution was taken and ultrasonicated for 60 min to form a suspension. Then 20 mg of acidified MWCNT (m γ-GY :m MWCNT =3:1), and 0.3mL of pyrrole (re-distilled before use). The mixture was ultrasonicated at 15°C for 60min to form a uniform dispersion. The mixture was then placed in a 10mL reactor and kept at a constant temperature of 180°C for 24h. After the reaction, a γ-GY / MWCNT composite hydrogel was obtained. The obtained γ-GY / MWCNT composite hydrogel was then solvent exchanged with anhydrous ethanol and deionized water for 5d to remove all impurities, and then freeze-dried for 12h to obtain a γ-GY / MWCNT composite aerogel catalyst.

[0070] Example 4

[0071] The present invention provides a method for preparing an oxygen reduction composite aerogel catalyst, and the specific preparation steps are as follows:

[0072] Under nitrogen (purity ≥ 99%) gas environment, the substrate hexabromobenzene (551.5 mg, 1 mmol), butynedioic acid (1140.6 mg, 10 mmol), catalyst bistriphenylphosphine palladium dichloride (210.6 mg, 0.3 mmol) and cuprous iodide (114.3 mg, 0.6 mmol) were placed in a Schlenk bottle; solvent N, N-dimethylformamide (10 mL) and triethylamine (2.1 mL) were added to dissolve. The solution was evacuated (4 times, 25 s each time) and stirred at 60 ° C for 24 h; after the reaction, a black solid was produced, which was then centrifuged, ultrasonicated with benzene, and repeatedly washed with N, N-dimethylformamide and a large amount of water until the centrifuge liquid was transparent and colorless, and the crude product γ-graphite monoyne was obtained by filtration; the crude product was refluxed with 6M sodium hydroxide for 2 h, then refluxed with 4M hydrochloric acid for 2 h, and finally refluxed with 6M sodium hydroxide for 2 h, and then filtered and evaporated to obtain the target product γ-GY.

[0073] Mix according to the ratio of m(γ-GY):m(KMnO4):V(H2SO4):V(HNO3) of 500mg:500mg:75mL:25mL. First, mix concentrated H2SO4 and concentrated HNO3, and slowly add γ-GY after cooling to room temperature, and then add KMnO4 in small amounts and multiple times. Stir the mixture vigorously in an 80℃ oil bath for 24h. After the reaction, cool the mixture to room temperature, and then neutralize it with NaOH in an ice bath to pH 8. A large amount of salt will be produced in the process. Use a filter membrane with a larger pore size to remove most of the salt by suction filtration, concentrate the mixture, and use a dialysis bag to dialyze for one week to remove inorganic acid and all impurities, and then concentrate it to 10mg / mL to obtain the acidified γ-GY aqueous solution.

[0074] MWCNT (5g) and NaNO3 (3.5g) were suspended in concentrated H2SO4 (150mL), then stirred vigorously in an ice-water bath for 60min, and KMnO4 (20g) was added in small amounts several times. Then stirred at room temperature (25°C), 300mL of water was slowly added after 120min, and H2O2 (3%, 500mL) was added. After stirring for 60min, the solution was centrifuged at 10000rpm to precipitate the acidified MWCNT, and then purified by water dialysis for one week, and then centrifuged at 5000rpm for 10min to remove the undispersed carbon nanotube bundles. Finally, the acidified MWCNT powder was obtained by rotary evaporation.

[0075] 60 mL of 10 mg / mL acidified γ-GY aqueous solution was taken and ultrasonicated for 40 min to form a suspension. Then 100 mg of acidified MWCNT (m γ-GY :m MWCNT =6:1), and 1.5mL of pyrrole (re-distilled before use). The mixture was ultrasonicated at 30°C for 40min to form a uniform dispersion. The mixture was then placed in a 100mL reactor and kept at a constant temperature of 240°C for 36h. After the reaction, a γ-GY / MWCNT composite hydrogel was obtained. The obtained γ-GY / MWCNT composite hydrogel was then solvent exchanged with anhydrous ethanol and deionized water for 10d to remove all impurities, and then freeze-dried for 30h to obtain a γ-GY / MWCNT composite aerogel catalyst.

[0076] Application Example 1

[0077] Fuel cell oxygen reduction (ORR) catalytic performance test.

[0078] It should be noted that the catalysts to be tested in this application example are all prepared in Example 1.

[0079] To ensure that the ORR performance of the prepared catalyst is accurately evaluated, we used a three-electrode system for testing. The core components of this system include: a glassy carbon rotating disk electrode (RDE) as a working electrode, on which the catalyst to be tested is loaded; a graphite electrode as a counter electrode, which together with the working electrode forms a current loop; and an Ag / AgCl electrode (in a saturated KCl solution) as a reference electrode to provide a stable potential reference. The disk area of ​​the glassy carbon rotating disk electrode is accurate to 0.1928 cm 2 Before the experiment begins, the pretreatment of the glassy carbon rotating disk electrode is crucial. The electrode surface is carefully polished with 0.05μm alumina polishing powder to remove surface impurities and oxides, exposing a clean and more active electrode surface. Subsequently, the electrode is thoroughly cleaned with distilled water to ensure that there is no residue on the surface, creating a clean and stable test environment for subsequent ORR performance testing.

[0080] (1) Cyclic voltammetry (CV) test: 500 mL of 0.1 mol / L KOH solution was prepared as the electrolyte solution, ultrasonicated for 30 min, and nitrogen was introduced for 30 min until saturated; 5 mg of catalyst was weighed and placed in a mixture of 750 μL of ethanol, 250 μL of water and 5% Nafion, mixed and ultrasonicated for 30 min to prepare a uniformly dispersed catalyst slurry, and then 10 μL of the slurry was pipetted with a pipette and dropped on a rotating disk electrode (RDE) and dried naturally. At this time, the catalyst loading on the electrode was 0.05 mg (0.26 mg / cm 2 ); During the experiment, the working voltage range of the cyclic voltammetry (CV) curve was -0.8 to 0.2 V, and the scan rate was 50 mV / s.

[0081] (2) Linear sweep voltammetry (LSV) test: 500 mL of 0.1 mol / L KOH solution was prepared as the electrolyte solution, ultrasonicated for 30 min, and oxygen was introduced for 30 min until saturated; 5 mg of catalyst was weighed and placed in a mixture of 750 μL of ethanol, 250 μL of water and 5% Nafion, mixed and ultrasonicated for 30 min to prepare a uniformly dispersed catalyst slurry, and then 10 μL of the slurry was pipetted with a pipette and dropped on a rotating disk electrode (RDE) and dried naturally. At this time, the catalyst loading on the electrode was 0.05 mg (0.26 mg / cm 2 ); the working voltage range of the linear sweep voltammetry (LSV) curve test was -0.8 to 0.2 V, the scanning rate was 5 mV / s, and the rotation speed was 1600 rpm.

[0082] Depend on Figure 8 It can be seen that the cyclic voltammetry curves of the samples in N2 saturated solution have no obvious reduction peaks, indicating that the samples have no catalytic effect on N2.

[0083] Depend on Fig. 9 It can be seen that the cyclic voltammetry curve of the sample in O2 saturated solution has an obvious ORR peak, indicating that the sample can reduce O2.

[0084] from Fig.10 It can be seen that the starting potential of γ-GY / MWCNT aerogel is 0.660V and the half-wave potential is 0.413V. In the ORR reaction, the half-wave potential is an important parameter, which reflects the overpotential required by the catalyst to reach a specific current density. The more positive the half-wave potential is, the smaller the overpotential required by the catalyst is when the same limiting current density is reached. This further shows that the catalytic activity of the catalyst is higher and can more effectively promote the ORR reaction. Therefore, it is inferred that γ-GY / MWCNT aerogel exhibits higher catalytic activity in the ORR reaction, which is due to its superior electrochemical properties. This conclusion provides strong support for the application of γ-GY / MWCNT aerogel as an efficient ORR catalyst.

[0085] Depend on Fig.11 It can be seen that the Tafel slope of the sample is measured to be 67.91mV·dec -1 . The significance of this value is that it reflects the kinetic characteristics of the catalyst in the ORR reaction. Generally, the lower the Tafel slope, the faster the kinetic process of the catalyst for the ORR reaction and the higher the reaction activity. Therefore, we can conclude that the Tafel slope of γ-GY / MWCNT aerogel is low, which fully proves its high performance in the ORR reaction. This finding provides a strong experimental basis for the application of γ-GY / MWCNT aerogel as an efficient ORR catalyst.

[0086] Through ORR testing, we conducted an in-depth study on the electrocatalytic performance of γ-GY and its composite aerogel with MWCNT. The experimental results show that although γ-GY itself has a certain ORR ability, its performance is not outstanding. When we added a small amount of MWCNT to it and made it into aerogel, its electrocatalytic performance was significantly improved (e.g. Fig.12). This significant performance improvement is mainly attributed to the synergistic effect between MWCNT and γ-GY. MWCNT not only has excellent conductivity and mechanical strength, but also provides a large number of attachment sites for γ-GY, thereby increasing the contact area between the catalyst and the reactant. At the same time, the layered three-dimensional structure of the aerogel further increases the specific surface area of ​​the sample, providing more active sites for the ORR reaction. In addition, the addition of pyrrole, on the one hand, promotes the gelation of the material, and on the other hand, realizes the doping of N atoms, thereby improving the activity and stability of the catalytic oxygen reduction reaction. After γ-GY is made into aerogel, it not only retains its original characteristics such as light weight and large surface area, but also adds advantages such as high aspect ratio, straight edges, few basal defects, and ideal surface rules. These characteristics make γ-GY / MWCNT aerogel superior to γ-GY alone in structure and performance, and more suitable as a functional material for electrocatalysis such as ORR reaction.

[0087] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a composite aerogel-type oxygen reduction catalyst, characterized in that: The following steps are involved: S1, ultrasonically treating an acidified γ-graphite aqueous solution to form a suspension, and mixing the acidified γ-graphite suspension with acidified multi-walled carbon nanotubes and pyrrole to form a dispersion; S2, using the dispersion prepared in S1 to prepare a γ-graphene monoacetylene / multi-walled carbon nanotube composite hydrogel by a hydrothermal method; S3, purifying and freeze-drying the hydrogel obtained in S2 to obtain a γ-graphite monoacetylene / multi-walled carbon nanotube composite aerogel catalyst.

2. The method for preparing a composite aerogel-type oxygen reduction catalyst according to claim 1, characterized in that: In S1, the concentration of the acidified γ-graphite monoacetylene aqueous solution is 5 to 20 mg / mL, and the ultrasonic time for preparing the suspension is 10 to 60 min.

3. The method for preparing a composite aerogel-type oxygen reduction catalyst according to claim 1, characterized in that: In S1, the time of the ultrasonic treatment after mixing is 10 to 60 minutes, and the temperature of the ultrasonic treatment after mixing is 15 to 50°C.

4. The method for preparing a composite aerogel-type oxygen reduction catalyst according to claim 1, characterized in that: In S1, the mass ratio of the acidified γ-graphite monoyne to the acidified multi-walled carbon nanotubes in the acidified γ-graphite monoyne aqueous solution is 1 to 6:

1.

5. The method for preparing a composite aerogel-type oxygen reduction catalyst according to claim 1, characterized in that: In S1, the volume ratio of the acidified γ-graphite monoacetylene aqueous solution to pyrrole is 40:1-6.

6. The method for preparing a composite aerogel-type oxygen reduction catalyst according to claim 1, characterized in that: In S2, the size of the hydrothermal kettle used in the hydrothermal method is 10-100 mL, the reaction temperature is 120-240° C., and the reaction time is 24-72 h.

7. The method for preparing a composite aerogel-type oxygen reduction catalyst according to claim 1, characterized in that: In S3, the specific steps of purification include: the hydrogel obtained in S2 is washed by exchanging deionized water and ethanol solvent, and the washing time is 5 to 10 days.

8. The method for preparing a composite aerogel-type oxygen reduction catalyst according to claim 1, characterized in that: In S3, the freeze-drying time is 12 to 36 hours.

9. A composite aerogel-type oxygen reduction catalyst prepared by the method according to any one of claims 1 to 8.

10. Use of the composite aerogel oxygen reduction catalyst prepared by the method according to any one of claims 1 to 8 in a fuel cell.

Citation Information

Patent Citations

  • Graphite carbon oxygen reduction electro-catalysis nano material as well as preparation method and application thereof

    CN115924900A

  • Low-platinum graphene oxygen reduction catalyst as well as preparation method and application thereof

    CN115986148A